Back Transfer of Infants with Tracheostomies: A Regional Center Experience - Attar, Mohammad A.; Pace, Rachael A.; Schumacher, Robert E. (Journal of Pediatric Intensive Care, 2021)
We describe our center's experience with the back transfer of infants following tracheostomies. We conducted a retrospective cohort study of infants transferred to pediatric critical care units of our regional center with conditions originating in the neonatal period who underwent tracheostomy during the hospitalization within their first year of life between 2006 and 2017. Recovering patients are discharged home or transferred back to the referring hospitals. We evaluated patient characteristics, destination of discharge and type of pulmonary support at discharge, and mechanical ventilation (MV) or tracheotomy masks (TM). Of the 139 included patients, 72% were transferred to the neonatal intensive care unit, 21% to the pediatric cardiothoracic unit, and 7% to the pediatric intensive care unit. Their median gestational age was 35 weeks. They were admitted at a median 22 days of life and lived at a median distance of 56 miles from our center. Furthermore, 34 infants (24%) were back transferred closer to their homes (23 with MV and 11 with TM), and 84 (60%) were discharged home (53 on MV and 31 on TM). Twenty-one patients (15%) died in the hospital (before discharge or transfer). Back transferred patients on MV had a significantly shorter duration between tracheostomy and transfer compared with those discharged home from our center: MV (median = 22 vs. 103 days, p < 0.0001) and TM (median = 13 vs. 35 days, p < 0.0001). Back transfer of infants with tracheostomies closer to their homes was associated with a significantly shorter hospitalization and more efficient use of the subspecialized resources at the RC.
Keywords: utilization; access; safety; counseling; neonatal; resource